Is there a group of patients at greater risk for hematoma following thyroidectomy? A systematic review and meta‐analysis. (2nd August 2016) - Quimby, Alexandra E.; Wells, Simon T.; Hearn, Matthew; Javidnia, Hedyeh; Johnson‐Obaseki, Stephanie
Abstract : Objective: The purpose of this study was to perform a systematic review and meta‐analysis to determine whether a difference exists in hematoma rates following thyroidectomy for any of the following subgroups of patients: Graves disease, toxic nodular goiter (TNG), and malignancy. Study Design: Systematic review and meta‐analysis. Methods: A systematic literature search was performed for all relevant English and French language studies (1946–2015) using Ovid MEDLINE, EMBASE, and PubMed. Three authors independently extracted data and analyzed articles for quality using the Newcastle‐Ottawa Quality Assessment Scale. Our primary outcome of interest was hematoma requiring re‐operation. Results: A total of 301 studies were screened, with 11 studies meeting the inclusion criteria. The results of our analysis demonstrated that Graves disease is the only indication for thyroidectomy that appears to have an increased risk of postoperative hematoma formation, pooled odds ratio = 1.58 (1.09–2.31); P = 0.02. Malignancy and TNG did not demonstrate significantly higher rates of postoperative hematoma formation. Conclusion: This study demonstrates that of patients undergoing thyroidectomy, Graves disease is the only indication in which patients are at increased risk of postoperative hematoma formation. This information may help guide future decisions regarding the implementation of outpatient thyroidectomy. Level of Evidence: NA. Laryngoscope, 127:1483–1490, 2017